Pengaruh Pendapatan, Persepsi Suku Bunga Kredit Dan Persepsi Kemudahan Syarat Pinjaman Kredit Terhadap Permintaan Kredit Pada PNM Mekaar di Kecamatan Cimanggu, Kabupaten Cilacap - lauralia, tamara; Kadarwati, Nunik; Supadi, Supadi (Lingka Ekonomika, 2022)
The purpose of this study was to analyze the effect of income, perceptions of loan interest rates, and perceptions of the ease of credit loan terms on credit demand at PNM Mekaar in Cimanggu District, Cilacap Regency. The respondents of this study were 97 people who were PNM Mekaar customers in Cimanggu District. Data collection techniques used are direct interviews and questionnaires. As for the data analysis technique used multiple linear regression technique. The results of this study indicate that income, perceptions of credit interest rates, and perceptions of the ease of credit loan terms together have a significant effect on credit demand at PNM Mekaar. While partially, income has a significant positive effect on credit demand at PNM Mekaar. Perceptions of credit interest rates have a negative but not significant effect on credit demand at PNM Mekaar. Perceptions of the ease of credit loan terms have a significant positive effect on credit demand at PNM Mekaar. The implication of this research is that PNM Mekaar should continue to improve business assistance to customers in order to deveop their business, so as to increase customer income. In addition, PNM Mekaar should maintain the ease of loan terms.